2013
DOI: 10.1309/ajcpmf26abeoychz
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of the Performance of the QIAGEN EGFR RGQ and EGFR Pyro Assays for Mutation Analysis in Non–Small Cell Lung Cancer

Abstract: Both the RGQ real-time PCR and Pyro assays adequately detect common EGFR mutations; however, the RGQ system is more clinically and analytically sensitive. Performance characteristics should be considered when evaluating these EGFR mutation assays for clinical adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…24 However, the limit of detection of the commercial kit was 5% for all the tumor samples 25 and EGFR RGQ Amplification Refractory Mutation System Scorpions probe-based real-time PCR assay is more clinically and analytically sensitive. 26 Intriguingly, we could not detect 41 FFPE samples using direct sequencing due to the low sensitivity. Although the sensitivity of real-time PCR is superior to direct sequencing, we found that 10 FFPE samples failed to detect EGFR mutations using real-time PCR.…”
Section: Discussionmentioning
confidence: 92%
“…24 However, the limit of detection of the commercial kit was 5% for all the tumor samples 25 and EGFR RGQ Amplification Refractory Mutation System Scorpions probe-based real-time PCR assay is more clinically and analytically sensitive. 26 Intriguingly, we could not detect 41 FFPE samples using direct sequencing due to the low sensitivity. Although the sensitivity of real-time PCR is superior to direct sequencing, we found that 10 FFPE samples failed to detect EGFR mutations using real-time PCR.…”
Section: Discussionmentioning
confidence: 92%
“…Forty-seven percent and 79% of p.T790M-mutated specimens had MAFs less than 10% and 20%, respectively, which is below the limit of detection for Sanger sequencing. Twenty-four percent of p.T790M-mutated specimens had MAFs of 1–5% which is below the limit of detection for pyrosequencing, high resolution melting analysis or real-time PCR assays such as the therascreen EGFR RGQ PCR Kit and cobas EGFR Mutation Test [3234]. In addition, these assays require separate runs for the detection of p.T790M and other EGFR mutations and therefore may not be suitable for comprehensive mutational profiling in core biopsy or fine needle aspiration specimens where tumor tissue is often limited.…”
Section: Discussionmentioning
confidence: 99%
“…This was not detected by direct Sanger sequencing, indicating that T790M occurred as a low level somatic mutation. The Qiagen EGFR RGQ is highly sensitive, and for T790M mutation in particular, the kit can detect mutant tumor alleles as low as 7% . This is unlike Sanger sequencing which generally has a detection limit of ∼20–25% mutant alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The Qiagen EGFR RGQ is highly sensitive, and for T790M mutation in particular, the kit can detect mutant tumor alleles as low as 7%. 13 This is unlike Sanger sequencing which generally has a detection limit of 20-25% mutant alleles. The failure of previous studies to identify such nonsynonymous EGFR mutations could be attributed to the use of the less sensitive Sanger sequencing methods.…”
Section: Ca S E Re P O Rtmentioning
confidence: 99%